Parasites Identification and Histopathology Changes on Blood Cookle (Anadara granosa Linnaeus, 1758) - Yuni Karnisa; Desrina Desrina; Ita Widowati (Marine Science Department Diponegoro University, 2019)
Blood cockle Anadara granosa is a popular sea food in Indonesia and potential for aquaculture. Currently, blood cockle aquaculture is at early stage, done by taking the larva from wild and raised them in the pond. Wild animal naturally carries parasites without outward clinical signs but can cause disease problem under aquaculture condition. This study aimed to identify parasites and histopathology changes in wild A. granosa. Blood cockles (n=90) were randomly collected during 3 months at three stations in the coastal waters of Bedono (Station 1: the intertidal area of the edge near to the mangrove area, station 2: the center of intertidal area, station 3: the area near to the sea), a village located on North Java coast and supplied blood cockle larva to the area. Parasites examination was conducted in the laboratory by macroscopic (observation of clinical symptoms) for ectoparasites and microscopic (using a microscope) for endoparasites. Histopathology preparation was done by taking three cockles at each station and cutting tissue that includes gills, foot, gonads, digestive tract and mantle. Organs were fixed in a 10% NBF solution, processed, mounted in paraffin and stained with hematoxylin and eosin. Parasites found were identified and the level of intensity and prevalence were calculated. There were three species of parasites found: Pinnotheres sp. (Intensity 1 ind/cockle; Prevalence: 3.33%), Perkinsus sp. (Intensity: 9.3 cell/cockle; Prevalence: 37.03%), Nematopsis sp. (Intensity: 4.25 cell/cockle; Prevalence: 29.62%). There were no histopathology changes on infected tissues which may relate to low diversity, prevalence and intensity of parasites found in this study.